Analisis Surat Dakwaan Penuntut Umum dalam Tindak Pidana Kekerasan Dalam Rumah Tangga - Siti Umayaroh (University of Jember, 2016)
The indictment is an authentic deed required for the commencement of criminal procedure proceedings. Therefore, the preparation and application of indictments by the prosecutor against the defendant must be following the provisions of the Criminal Procedure Code, as Article 143 explains that the indictment must contain formal conditions and material requirements. If it does not meet material requirements, the indictment shall be null and void. When the indictment no longer complies with the prevailing laws and regulations. Thus, it will affect the weakness of law enforcement in Indonesia and an error in Juris. This article contains 2 (two) issues, namely: (1) Whether the application of Article 351 paragraph (1) of the Criminal Code or Article 365 paragraph (2) number 1 and 3 of the Criminal Code in cases of domestic violence is following the principle lex specialis derogat legi generalist? (2) Is the alternative indictment formulated by the public prosecutor following the defendant's conduct? This research uses normative juridical research, by using a statute approach and conceptual approach. Obtained results and conclusions in writing this article that the application of the prosecutor's indictment in cases of domestic violence is not following the principle of lex specialis derogat legi general and the preparation of indictment letter in the form of an alternative not following the actions of the defendant. KEYWORDS: The Defendant, Error In Juris , The Principle Of Lex Specialis Derogat Legi Generalis.